Socio-environmental multi-labelling and consumer willingness to pay. (September 2014) - Dufeu, Ivan; Ferrandi, Jean-Marc; Gabriel, Patrick; Le Gall-Ely, Marine
The objective of this article is to assess the impact of a gradual increase in the number of labels appearing on some food products on consumer valuation of the given product. Three empirical studies were designed to measure the effects of using labels to differentiate food products (Organic Farming, Fairtrade, and Label Rouge (a French label that concerns organoleptic quality)) on the willingness of 519 French consumers of honey to pay a premium. These three studies shed light on a complementarity effect, often dominating the effects of redundancy and information overload. This effect differed depending on the features and the number of associated labels, and was influenced by consumer trust in the labels. These findings should encourage producers to associate their products with labels on packaging when they are consistent in terms of reputation but complementary in terms of attributes.